Associations between physical activity, fitness, cognitive and academic performance in Swedish adolescents: Findings from a cross-sectional study - Karin Kjellenberg; Rui Wang; Jonna Nilsson Horre; Björg Helgadóttir; Örjan Ekblom; Amika Singh; Gisela Nyberg (PLoS ONE, 2026)
Background Adolescence is a crucial phase for the development of cognitive abilities linked to academic performance. Factors such as physical activity (PA) and fitness have been hypothesized to be linked to these outcomes, although the evidence is inconclusive. This study aimed to examine the associations between PA, fitness, academic, and cognitive performance in the same sample of adolescents. Methods In this cross-sectional study, 1139 Swedish adolescents (mean age 13.4 years) participated. We assessed PA (accelerometry), cardiovascular fitness (submaximal ergometer test), cognitive performance (computer-based test assessing episodic and working memory with 3 tests per domain), and academic performance (grades in math and language, Swedish). We utilized multilevel mixed models to explore associations and structural equation modeling to perform mediation analyses. Results We found a weak positive association between cardiovascular fitness and math grades (b: 0.18, 95% CI: 0.09, 0.26 β: 0.18), language grades (b: 0.16, 95% CI: 0.07, 0.25 β: 0.13), and cognitive performance (b: 0.01, 95% CI: 0.00, 0.02 β: 0.11). Further, cognitive performance scores mediated 40% of the associations between fitness and math, and language grades. Adolescents with parents with short education (≤12 years of education) or foreign-born had lower fitness levels and grades in math and language (all p < 0.05). Conclusion Fitness was the only significant factor associated with cognitive and academic performance, although the association was weak. Given our findings of low fitness and academic performance among adolescents with parents with short education or parents born abroad, future studies should tailor their interventions to ensure the inclusion of these groups.